2022
DOI: 10.3390/s22207998
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture, Organic Carbon, and Nitrogen Content Prediction with Hyperspectral Data Using Regression Models

Abstract: Soil moisture, soil organic carbon, and nitrogen content prediction are considered significant fields of study as they are directly related to plant health and food production. Direct estimation of these soil properties with traditional methods, for example, the oven-drying technique and chemical analysis, is a time and resource-consuming approach and can predict only smaller areas. With the significant development of remote sensing and hyperspectral (HS) imaging technologies, soil moisture, carbon, and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…The Random Forest (RF) algorithm has been used in several studies related to crop classification, which has demonstrated good performance [21]. Additionally, the RF algorithm has produced reliable results in numerous investigations that predicted soil properties using regression models [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Random Forest (RF) algorithm has been used in several studies related to crop classification, which has demonstrated good performance [21]. Additionally, the RF algorithm has produced reliable results in numerous investigations that predicted soil properties using regression models [22].…”
Section: Introductionmentioning
confidence: 99%
“…The data produced by hyper-spectral cameras are not only useful for investigating the reflected spectral intensity of green plants but also for analyzing the chemical properties of ground targets. Hyper-spectral data can provide information about the chemical composition and water content of soil [48], as well as the chemical composition of ground minerals [49,50]. This is because hyper-spectral cameras can capture data across many narrow and contiguous wavelength bands, allowing for detailed analysis of the unique spectral signatures of different materials.…”
Section: Multi-spectral and Hyper-spectral Cameramentioning
confidence: 99%
“…In the study, the authors found that the effect of estimating soil water content using multi-spectral data was better than that using thermal imaging data, with a correlation coefficient R 2 = 96%. Datta et al [48] studied the relationship between hyper-spectral image data and soil moisture content. Based on all hyper-spectral band (AHSB) data, the authors used support vector regression (SVR) [148], which achieved a result correlation coefficient R 2 = 95.43%, RMSE = 0.8.…”
Section: Soil Water Contentmentioning
confidence: 99%
“…Both principal components regression (PCR) and PLSR are linear chemometric tools used for the analysis of spectroscopic data for different applications. They are the most common modeling techniques for quantitative spectroscopy analyses in soils and have been extensively discussed in the literature [24][25][26]. They both represent techniques that are based on the decomposition of the spectral data into features that capture most of the variance that exists in the raw visible and near-infrared spectroscopic (VIS-NIRS) data and the creation of linear models using the scores of the most correlated features [27].…”
Section: Introductionmentioning
confidence: 99%